Do single people want to date a cancer survivor? A vignette study - Tuinman, Marrit Annika; Lehmann, Vicky; Hagedoorn, Mariët (PLOS ONE, 2018)
Objective Qualitative studies indicated that cancer survivors may be worried about finding a partner in the future, but whether this concern is warranted is unknown. We examined single people´s interest in dating a cancer survivor, how they perceive survivors’ traits, and their preferences about the timing of disclosing a cancer history. Methods In three experimental vignette studies, dating website members (n = 324) and college students (n = 138 and n = 131) were randomly assigned to a vignette of a person with or without a history of cancer (experiment 1 & 2), or a cancer survivor beyond or during active follow-up (experiment 3). Respondents rated their interest in dating this fictive person, this person’s traits, and indicated their preferences about the timing of disclosure. ANOVAs with main and interaction effects of condition, gender, and relationship history were conducted, partial eta squared and Cohen’s d were used to estimate the magnitude of effects. Correlations were used to investigate relationships between interest in a date and assessment of traits. Results Cancer survivors’ traits were assessed more positively, but interest to date them did not differ from healthy vignettes for both men and women. However, widowed respondents were much less interested in a date with a cancer survivor, and women showed less interest in a cancer survivor during active follow-up relative to survivors beyond follow-up. Most respondents wanted to hear about the cancer diagnosis after a few dates, hardly anyone wanted to hear about this before the first date (2% - 5%). Conclusion and implications for cancer survivors Cancer survivors do not have to expect any more problems in finding a date than people without a cancer history, and can wait a few dates before disclosing. Survivors dating widowed people and survivors in active follow-up could expect more hesitant reactions and should disclose earlier.